IDENTIFICATION OF PACEJKA MODEL PARAMETERS OF A LIGHT COMMERCIAL VEHICLE TIRE FOR DYNAMIC RESEARCH - Toropov, Eugeny; Vashurin, Andrey; Tumasov, Anton; Butin, Danila; Stepanov, Evgeniy (Journal of Applied Engineering Science, 2023)
This article is devoted to the research of the interaction of the wheel of a GAZ light commercial vehicle with a hard supporting surface. The relevance of this problem is due to the need to adequately reproduce the force reactions acting on the tire in the contact patch, when modelling the vehicle dynamics. High similarity of the real process and its modelling are guaranteed if there is a significant empirical data set for a particular tire model, which can be ensured only by the results of field tests. Specialists from Nizhniy Novgorod State Technical University have developed a schematic diagram of a road measuring unit, a test methodology and built testing unit as well as conducted full-scale tests. The experiment was conducted in the auto racing track at an ambient air temperature of 20 °C on a dry road asphalt surface with a high friction coefficient (0.4 – 0.8). The resulting array of experimental data was processed and presented in numerical trigonometric polynomials form (PAC 2002). The table comparing theoretical and experimental values presented in the results of this article confirms the high level of convergence. The maximum discrepancy in absolute value does not exceed 5%.
Keywords: slip ratio, field testing, braking, modelling, “magic” formula